(untitled) (Advances in Knowledge Representation, 2022)
In the context of public security, it is up to the intelligence activity, the permanent and systematic production and safeguarding of knowledge with the objective of advising the decision-making level of police organizations. There is a gap in Information Science with regard to research on inter-organizational knowledge sharing, specifically aimed at public security intelligence activity. From the bibliographic and documental review, a description of the current state of knowledge management is presented, from the perspective of its sharing, in the public security intelligence system of the state of Minas Gerais. Among the results obtained, it was found that the effective intelligence agencies of this system perform the collection and analysis of data and information to produce knowledge in support of decision making. However, it was also found that these agencies need to deepen their understanding of how interorganizational knowledge sharing occurs, in order to adopt more effective strategies and public policies in this sense.